Effectiveness of Antioxidants and Resistance to Diamondback Moth Infestation in Green Mustard Plants Using Ethanol Extracts from Millettia pachyloba Drake Leaves: An In Vitro and In Vivo Evaluation - Tran Thi Phuong Nhung; Le Pham Tan Quoc (Caraka Tani: Journal of Sustainable Agriculture, 2025)
The growing interest in medicinal plants as sustainable alternatives to synthetic pesticides has led to the exploration of Millettia pachyloba (MPDE) for pest management. This study aims to evaluate the effectiveness of MPDE in controlling Diamondback moth (DBM) infestation and enhancing oxidative stress tolerance in green mustard plants. The goal is to determine MPDE’s potential to improve pest resistance and mitigate plant oxidative stress. The experiment involved applying MPDE at concentrations of 2, 4, 6, 8, and 10% (w/v) to DBM larvae and green mustard plants, with fipronil 5% SC and water as controls. In vitro, the effects of MPDE on DBM larvae were assessed using bioassays, including oviposition, feeding preferences, and insecticidal activity. In vivo, MPDE was sprayed on green mustard plants infested with DBM larvae, and plant growth, survival, and yield were monitored. Antioxidant activity was measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and reducing power assays. The results of the study at p < 0.05 showed that MPDE significantly reduced oviposition and feeding by DBM, with higher concentrations demonstrating greater effectiveness. MPDE also increased DBM larval mortality, improved stem bending capacity, and enhanced plant survival, particularly at concentrations of 10%, which were comparable to fipronil. Moreover, MPDE exhibited significant antioxidant activity and reversed DBM-induced inhibition of antioxidant enzymes, reducing oxidative stress. These findings suggest that MPDE is a promising, eco-friendly alternative to chemical pesticides, enhancing pest resistance and oxidative stress tolerance in plants.